2013
DOI: 10.1111/ctr.12179
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term evaluation of autologous transplantation of bone marrow–derived mesenchymal stem cells in patients with cirrhosis: Egyptian study

Abstract: . Short-term evaluation of autologous transplantation of bone marrow-derived mesenchymal stem cells in patients with cirrhosis: Egyptian study.Abstract: Background: Stem cell-based therapy has received attention as a possible alternative to organ transplantation. The aim of this study was to assess the safety and efficacy of autologous transplantation of bone marrow (BM)-derived stromal cells in post-HCV liver cirrhosis patients. Methodology: 10 9 10 6 of isolated human bone marrow (HBM)-stromal cells in 10 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 20 publications
5
63
1
1
Order By: Relevance
“…In the field of liver cirrhosis, as shown in Table 1, many autologous [70][71][72][73][74][75][76][77][78][79][80][81][82][83] and four allogeneic [59][60][61][62] MSC therapies involving a variety of tissue origins and administration routes have been reported. Although details regarding the mechanisms of therapeutic effects in humans remain unclear, most studies have reported favorable effects with improvement in MELD scores, Child-Pugh scores, and some serum markers such as albumin and bilirubin.…”
Section: Mscsmentioning
confidence: 99%
“…In the field of liver cirrhosis, as shown in Table 1, many autologous [70][71][72][73][74][75][76][77][78][79][80][81][82][83] and four allogeneic [59][60][61][62] MSC therapies involving a variety of tissue origins and administration routes have been reported. Although details regarding the mechanisms of therapeutic effects in humans remain unclear, most studies have reported favorable effects with improvement in MELD scores, Child-Pugh scores, and some serum markers such as albumin and bilirubin.…”
Section: Mscsmentioning
confidence: 99%
“…Recently, a pilot study was conducted to evaluate the safety and efficacy of autologous BM-MSCs in 20 liver cirrhosis patients. These patients received an intrasplenic injection of 10 × 10 6 BM-MSCs and were monitored for 10 months [56]. This study further validated that autologous BM-MSC transfusion significantly improves liver function, whereby the serum bilirubin, AST and ALT levels, prothrombin time and International Normalized Ratio (INR) decreased, while serum albumin levels increased.…”
Section: Allogeneic Stem Cells In Liver Cirrhosis Therapymentioning
confidence: 59%
“…Similarly, recent study observed shortterm efficacy of autologous BM-MSCs transplantation in liver failure patients caused by viral hepatitis B. The liver function and MELD score were significantly improved in the transplantation group as compared to the control group for 2-3 weeks post-transplantation and these effects could sustain 36 weeks [87]. Currently, autologous BM-MSCs transplantation showed safety, feasibility and efficacy in improving liver function of Egyptian patients with cirrhosis.…”
Section: Clinical Trials In Humanmentioning
confidence: 78%